2019
DOI: 10.1021/acsnano.9b08205
|View full text |Cite
|
Sign up to set email alerts
|

Time Evolution Studies on Strain and Doping of Graphene Grown on a Copper Substrate Using Raman Spectroscopy

Abstract: The enhanced growth of Cu oxides underneath graphene grown on a Cu substrate has been of great interest to many groups. In this work, the strain and doping status of graphene, based on the gradual growth of Cu oxides from underneath, were systematically studied using time evolution Raman spectroscopy. The compressive strain to graphene, due to the thermal expansion coefficient difference between graphene and the Cu substrate, was almost released by the nonuniform Cu2O growth; however, slight tensile strain was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 56 publications
3
38
0
Order By: Relevance
“…The changes were known being more significant for the graphene structures exposed to gases such as NH 3 , CO, H 2 O and NO 2 [6]. There were reported attempts in literature [9][10][11] focused on understanding of the long-time stability problems. In [9], the changes in properties over time were described for the graphene sheets grown on the Cu substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes were known being more significant for the graphene structures exposed to gases such as NH 3 , CO, H 2 O and NO 2 [6]. There were reported attempts in literature [9][10][11] focused on understanding of the long-time stability problems. In [9], the changes in properties over time were described for the graphene sheets grown on the Cu substrate.…”
Section: Introductionmentioning
confidence: 99%
“…There were reported attempts in literature [9][10][11] focused on understanding of the long-time stability problems. In [9], the changes in properties over time were described for the graphene sheets grown on the Cu substrate. An influence of the atmosphere was explained for the graphene sheets in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that various studies have suggested that the values of ω G and ω 2D cannot be explained solely by charge doping and strain [ 67 ], and that variations in the Fermi velocity can alter the ω 2 D without affecting the ω G [ 61 , 68 ]. Finally, previous studies on the oxidation of graphene on Cu surfaces have attributed red-shifts in ω D , ω G and ω 2 D to strain release after oxidation, as mentioned previously, which augment with the growth of the oxide underlayer [ 20 , 48 ] producing corrugation and wrinkling in the graphene sheet [ 69 ]. In all these cases, characteristic Raman bands of copper oxides were clearly observed, where the strongest bands expected for Cu 2 O at 148, 219 and 635 cm -1 , and CuO at 273, 327 and 619 cm -1 [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 69%
“…[53] By plotting the G-band (ω G ) against the 2D-band (ω 2D ) frequencies using the Raman maps in Figure S6, Supporting Information, vector analysis on strain and doping was conducted depending on the transfer methods in Figure 6. [54,55] Incremental strain and doping levels (i.e., 0.1% and 5 × 10 12 cm −2 , respectively) are marked in black and pink horizontal lines along two unit vector directions, e H and e T . Interestingly, four samples display different characteristics in doping and strain status.…”
Section: Figure 2amentioning
confidence: 99%